Characteristics of hybrid systems for electricity generation and applications in wind-photovoltaic systems - Siqueira, Jair Antonio Cruz; Gabriel Filho, Luís Roberto Almeida [UNESP]; Caneppele, Fernando de Lima; Seraphim, Odivaldo José [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2014)
A hybrid system uses jointly more than one source of energy for the generation of electricity in which one source complements the eventual failure of the other. The system may be a combination of one or more forms of generation, employing wind power, solar photovoltaic systems, diesel, water, or others, even though energy storage system is not mandatory. Solar and wind power system may be underscored among the energy sources used by hybrid systems since they feature renewable characteristics. The success of their implementation depends directly on the reliability of the operation to the power supply and to the cost of the energy produced. Current study introduces several systems´ characteristics for the generation of electricity. Regarding system design, it is important to analyze costs and usages of the system coupled to electrical system factors, such as charge loss and battery life. A photovoltaic-wind system was built at the Faculty of Agronomic Sciences of Botucatu (UNESP) to disseminate and specify the components of a hybrid system for the generation of electric power. Several research works were performed at the Center for Alternative and Renewable Energies of the Laboratory for Rural Energy of the Agricultural Engineering Department in Botucatu SP Brazil.

Um sistema híbrido é aquele que utiliza conjuntamente mais de uma fonte de energia para geração de energia elétrica, sendo que tal opção é feita de modo que uma fonte complemente a eventual falta da outra. Tais sistemas podem ser combinações de uma ou mais formas de geração, podendo ser usados sistemas eólicos, fotovoltaicos, diesel, hídricos, ou outros, sendo a opção do armazenamento energético não obrigatória. Dentre as fontes energéticas utilizadas pelos sistemas híbridos, as que mais se sobressaem são a solar e a eólica, ambas de caráter renovável. O sucesso de sua implantação depende diretamente da confiabilidade da operação ao fornecimento de energia e do custo da energia gerada. O objetivo deste trabalho foi apresentar diversas características de tais sistemas de geração de energia elétrica. Em relação ao dimensionamento do sistema, mostrou-se que é importante a análise de custos e formas de utilização do sistema, bem como fatores elétricos do sistema, tais como perda de carga e vida útil da bateria. Como forma de divulgação e especificação dos componentes de um sistema híbrido de geração de energia elétrica, foi eleito um sistema eólico fotovoltaico localizado na Faculdade de Ciências Agronômicas de Botucatu, o qual possibilitou diversas pesquisas junto ao Núcleo de Energias Alternativas e Renováveis do Laboratório de Energização Rural do Departamento de Engenharia Rural da UNESP, Faculdade Ciências Agronômicas, Campus de Botucatu.
Características de sistemas híbridos de geração de energia elétrica e aplicações em sistemas eólicos fotovoltaicos
Keywords: Renewable energy; Reliable operation; System sizing; Components of a hybrid system; Energias renováveis; Confiabilidade da operação; Dimensionamento do sistema; Componentes de um sistema híbrido